Shoreface facies model of Cretaceous Jessu Formation, Yola Sub-basin, Northern Benue Trough, northeast Nigeria: New insights from facies analysis and molecular geochemistry. (April 2019) - Sarki Yandoka, Babangida M.; Abdullah, Wan Hasiah; Abubakar, M.B.; Johnson, Howard; Adegoke, Adebanji Kayode; Arabi, A.S.; Bata, Timothy P.; Amir Hassan, M.H.; Mustapha, Khairul Azlan; Usman, M.B.
Abstract: The Yola Sub-basin in the Northern Benue Trough is a frontier exploration basin in northeastern Nigeria and to date, there is no subsurface data available. The oldest sedimentary unit in the Yola Sub-basin is the Bima Formation, followed by Yolde, Dukul, Jessu, Sekuliye, Numanha and Lamja Formations, ranging in age from Berremian-Aptian-Albian to Santonian. The sediments of Jessu Formation were studied based on facies analysis (lithofacies and palynofacies) and geochemistry (biomarker distribution) with an objective of analysing and interpreting the source input/origin, paleodepositional conditions, paleodepositional environment and to reconstruct depositional and facis model for the studied successions. The study revealed that the sediments were deposited in a distal oxic-suboxic to relatively anoxic shelf (shallow marine) environment with both aquatic, -marine and terrestrially derived source inputs. Depositional framework indicate a progradational wave and storm-dominated shoreface-offshore facies succession, displaying a coarsening upward trend. This represent a regressive shoreface-offshore depositional system, consistent with earlier interpretations that the Cretaceous sediments of Jessu Formation were deposited during a brief regressive phase in the Northern Benue Trough. Highlights: Jessu Formation is a Cretaceous succession in the Yola Sub-basin. The sediments were deposited majorly under dysoxic shallow marine condition. Progradational wave and storm offshore-shoreface facies succession. Brief regressive offshore-shoreface facies sequences.